Construction of plasmids expressing specific genes of Mycobacterium tuberculosis: towards the development of vaccine against tuberculosis - Musa, Mustaffa; Ahmad, Salwana; Asan, Jamaruddin M.; Zainuddin, Zainul F. (2001)
The objective of the project was to oonstrud plasmid(s) expressing specific genes of Mycobacterium tuberculosis (MTB): towards the development of potential DNA vaccine candidates against tuberculosis.Several T-cell epitopes from various specific genes of MTB were selected which include ESAT-6, MTP40, MPT64 and 38k0a.In order to construct the synthetic gene consists of those selected epitopes, the innovative PCR technology known as 'Assembly PCR' was employed. In this project, the synthetic gene (consist of multiple epitopes of M. tuberculosis) was successfully constructed and the gene is designated as vacll.The vacll was then cloned into plasmid DNA vector, pJW4303.The recombinant plasmid containing the vacll designated as pJWvacll was obtained.The DNA sequence of the cloned gene(vacll) or the insert was confinned by DNA sequencing method.So, in this project,we have constructed one DNA vaccine candidate for tuberculosis. Further studies that to be done to evaluate this vaccine candidate include immunogenecity and protection efficacy in animal model.In this project, the immunogenicity of pJWvacll was studied in mice in order to determine its ability to induce various immune responses. Mice were immunised with the pJWvacll and control plasmid (pJW blank vector). At the end of the immunisation protocol, the spleenic lymhocytes were prepared from the two groups of mice. Lymphocyte responses in vitro were determined by Flow Cytometric analyses, Lymphocyte Transformation Test and IFN gamma production {by ELISA) after culturing them with several peptides derived from the vacll construct.Results of Flow Cytometry which measure lymphocyte activation status did not show any significant different between the control and test group. But, results of LTT and IFN gamma production showed that some mice vaccinated with pJWvacll were positive when compared to the control group. These results indicated that the DNA vaccine candidate (pJWvacll) is immunogenic in mice ie able to induce immune response. The ability of pJWvacll to induce IFN gamma production suggested that the DNA vaccine construct stimulated the Th1 type of immune response which is essential or immunity to TB. However, more studies need to be done to confirm these prilimanary findings. Such studies include protection or challenge studies in mice but this part of the study can be done here due to lack of facility required.